KITAB TURATH SEBAGAI LOCAL GENUINE TO HUMANIZING CHANGES - Harapandi, Dahri (Borneo International Journal of Islamic Studies, 2020)
Turath literally means to inheritance. Turath is also a treasure trove of intellectual traditions inherited by previous scholars and experts (al-Qudama?). The book Turath is also known as the yellow book and is the work of previous scholars, whether there are still manuscripts or in print. The book of turath can actually be a media that connects the past and present to the future, turath can show a classic face but produce modern works. The turath book is an intellectual property that is rich in pithy thoughts and ideas, in which are stored pearls of pearls which are very expensive. Practices and behavior patterns of the ancient people so that they are able to become lights for today's people are very well presented. Because of that the book Turath can be a window to the present that will be able to provide concepts and ideas of the past in order to be an inspiration for the future.